Urinary tract infections in diabetics with CKD: microbial profile and antibiotic resistance - Areej, Kiran; Fatima, Sadaf; Sreena, Maria; Muzammil, Muhammad; Javed, Hafiz Muhammad Hassam; Khan, Meer Hazar (Infectious Diseases Journal of Pakistan, 2025)
Background: Patients with diabetes and CKD are highly susceptible to UTIs owing to compromised immunity and urinary abnormalities. Rising antimicrobial resistance in this group complicates effective management and outcomes. The objective is to assess the prevalence of bacteriologically confirmed UTIs in diabetic patients with CKD and to characterize the spectrum of uropathogens and their antibiotic susceptibility patterns. Material and Methods: A cross-sectional analysis was conducted on 470 clean-catch midstream urine specimens collected from diabetic CKD patients. Urinary isolates were identified using conventional culture-based microbiological methods. Antimicrobial susceptibility testing was performed via the Kirby–Bauer disk diffusion technique, interpreted according to the CLSI criteria. Results: The study found a 16.6% prevalence of culture-confirmed UTIs in diabetic CKD patients, with E. coli as the predominant pathogen. High resistance to beta-lactams limited their empirical use, while carbapenems and polymyxins were effective against Gram-negative isolates, and vancomycin against Gram-positive organisms. These results highlight the importance of routine culture and sensitivity testing and underscore antimicrobial stewardship in managing UTIs in this high-risk group. Conclusion: Study reveals a high prevalence of UTI among diabetic patients with CKD, predominantly caused by MDR Gram-negative pathogens such as E. coli. Alarmingly high resistance rates were observed against commonly used antibiotics, including beta-lactams and fluoroquinolones, while carbapenems, polymyxins, and amikacin remained effective. These findings underscore the necessity for culture-guided therapy, judicious antibiotic use, and robust antimicrobial stewardship to improve patient outcomes and combat the growing threat of AMR in this vulnerable population. Keywords: UTIs, Diabetics, CKD, Microbial profile, Antibiotic resistance.